2001
DOI: 10.1046/j.1444-2906.2001.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interposition of pink muscle fiber into dorsal ordinary muscle on increasing rate of K-value in various fish species

Abstract: Twenty‐seven fish species from the Sakishima Islands and Nagasaki living in water temperatures of 28°C (12 fish species) and 17°C (15 fish species), respectively, were used as sample fishes. Postmortem temporal changes of K‐values were measured at 1‐h intervals in the dorsal ordinary muscle of each fish, of which the remaining body was then kept in water at a controlled temperature of 32°C. The increasing rate of K‐value at 32°C (ΔK32) was calculated from the regression line formed from the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…[14][15][16] As previously reported, the ordinary muscle part near the intermediate muscle layer in carp was composed of pink and of subtypes like IIa and IIb of white muscle fibers. 14,15 The pink muscle fibers, however, gradually decreased in number inwards, and became unrecognizable in the innermost part of ordinary muscle. 14,17 We have reported that the temporal change in Kvalue of carp was fastest in red, followed by pink, and white muscle fibers.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…[14][15][16] As previously reported, the ordinary muscle part near the intermediate muscle layer in carp was composed of pink and of subtypes like IIa and IIb of white muscle fibers. 14,15 The pink muscle fibers, however, gradually decreased in number inwards, and became unrecognizable in the innermost part of ordinary muscle. 14,17 We have reported that the temporal change in Kvalue of carp was fastest in red, followed by pink, and white muscle fibers.…”
Section: Introductionmentioning
confidence: 54%
“…Therefore, most histochemical studies have focused on these distinct layers, 8–13 and only a few have dealt with the different muscle fiber types in the ordinary muscle of fish. In a series of studies that we have recently conducted, we reported that the dorsal ordinary muscle in many fish species is composed of not only white but also pink muscle fibers arranged in a mosaic pattern 14–16 . As previously reported, the ordinary muscle part near the intermediate muscle layer in carp was composed of pink and of subtypes like IIa and IIb of white muscle fibers 14,15 .…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…The ordinary muscle of cultured carp near the intermediate muscle layer was composed of three muscle fiber types: the pink muscle fiber and white muscle fiber IIa and IIb subtypes, whereas the innermost ordinary muscle consisted only of white muscle fiber IIa and IIb subtypes . By contrast, the percentages of interposition of pink muscle fibers in the dorsal ordinary muscle were distributed widely, ranging from 0% to 56.5% in number and from 0% to 53.7% in area . It is well known that rigor mortis of the muscle after death occurs when the ATP concentration decreases to a level no longer sufficient to support the removal of the connection between myosin and actin filaments of the myofibrils .…”
Section: Discussionmentioning
confidence: 85%